FAKTOR YANG MEMPENGARUHI EEKTIVITAS PENGELOLAAN KEUANGAN BADAN LAYANAN UMUM DAERAH: FACTORS AFFECTING THE EFFECTIVENESS OF FINANCIAL MANAGEMENT OF REGIONAL GENERAL SERVICES AGENCY - Aini, Zahratul; Yasni, Hariadi (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2022)
This study aims to empirically examine the utilization of information technology, human resources competency, government financial accounting system, functional supervision, and internal control system for the effectiveness of financial management of BLUD. This research was conducted using a survey method through a questionnaire. The sampling technique used purposive sampling. The analysis technique used is multiple linear regression to examine the effect of using the variables. The results of this study indicate that: first, the use of information technology affects the effectiveness of the financial management of BLUD. Second, human resource competencies affect the effectiveness of the financial management of BLUD. Third. government financial accounting systems affect the effectiveness of financial management of BLUD. Fourth, functional supervision affects the effectiveness of the financial management of BLUD. Fifth, the government's internal control system affects the effectiveness of the financial management of BLUD